Autochthonous and allochthonous contributions of organic carbon to microbial food webs in Svalbard fjords. (27th March 2017) - Holding, Johnna M.; Duarte, Carlos M.; Delgado‐Huertas, Antonio; Soetaert, Karline; Vonk, Jorien E.; Agustí, Susana; Wassmann, Paul; Middelburg, Jack J.
Abstract: Rising temperatures in the Arctic Ocean are causing sea ice and glaciers to melt at record breaking rates, which has consequences for carbon cycling in the Arctic Ocean that are yet to be fully understood. Microbial carbon cycling is driven by internal processing of in situ produced organic carbon (OC), however recent research suggests that melt water from sea ice and glaciers could introduce an allochthonous source of OC to the microbial food web with ramifications for the metabolic balance of plankton communities. In this study, we characterized autochthonous and allochthonous sources of OC to the Western Svalbard fjord system using stable isotopes of carbon. We quantified δ 13 C of eukaryotic and prokaryotic planktonic groups using polar lipid‐derived fatty acids as biomarkers in addition to measuring δ 13 C of marine particulate OC and dissolved OC from glacial runoff. δ 13 C of bacteria (−22.5‰) was higher than that of glacial runoff OC (−28.5‰) and other phytoplankton groups (−24.7 to −29.1‰), which suggests that marine bacteria preferentially use a third source of OC. We present a Bayesian three‐source δ 13 C mixing model whereby ∼ 60% of bacteria carbon is derived from OC in sea ice, and the remaining carbon is derived from autochthonous production and glacial‐derived OC. These results suggest that subsidies of OC from melting glaciers will not likely influence microbial carbon cycling in Svalbard fjords in the future and that further research is needed to determine the effects of melting sea ice on microbial carbon cycling in fjord systems and elsewhere in the Arctic Ocean.